Development of a Mathematical Model of VMS for Automotive Structural Member using FEA-RSM Hybrid Modeling. (2016) - Patel, Tushar M.; Bhatt, N.M.
Abstract: The main aim of the research is to develop the mathematical model of von-Mises Stress (VMS) to optimize the weight of the chassis frame using FEA RSM hybrid modelling. Web thickness, upper flange thickness and lower flange thickness of the sidebar are considered as input parameters. Sets of parameters for chassis frame variants are designed by employing Response Surface Methodology (RSM) in statistical software, "MINITAB 16". The regression equation for VMS is developed using the Finite Element Analysis (FEA) results of different variants of the chassis frame. The analysis of variance (ANOVA) is performed to statistically analyze the results. The individual effects of parameters and the combined effects of multiple parameters are examined. Among the variable web thickness and lower flange had the most significant effect on the stress generated.